Deletions of SCN2A and SCN3A genes in a patient with West syndrome and autistic spectrum disorder. (August 2018) - Chong, Pin Fee; Saitsu, Hirotomo; Sakai, Yasunari; Imagi, Toru; Nakamura, Ryoko; Matsukura, Masaru; Matsumoto, Naomichi; Kira, Ryutaro
Abstract: SCN2A encodes the alpha-subunit of voltage-gated sodium channel, Nav1.2, which is highly expressed at an early stage of the postnatal brain. Genetic studies revealed that de novo heterozygous mutations of SCN2A caused severe developmental disorders in childhood, such as autism and epileptic encephalopathy. However, few reports have demonstrated the cases carrying segmental deletions at the SCN2A locus for those with epileptic disorders. In this study, we report a 1.8-year-old boy, who presented with West syndrome in infancy and developed the sequelae of psychomotor delay and autism. Since whole-exome sequencing did not detect pathogenic mutations, we extensively searched for microdeletions and duplications by applying the eXome Hidden Markov Model (XHMM) for read depths of sequenced intervals. Using this approach, we identified a de novo deletion spanning the 1.1-Mb region of chromosome 2q24.3. We found that the deleted interval included the SCN2A and SCN3A loci. These data validate the utility of XHMM and support that SCN2A is involved in the pathogenic processes underlying epileptic encephalopathy in childhood. Highlights: West syndrome is a heterogeneous epileptic disorder with poor prognosis. Deletion of SCN2A and SCN3A was detected in an autistic West syndrome child. SCN2A plays a critical role in the pathogenic processes of West syndrome and autism. XHMM is useful in identifying pathogenic copy number variants in epileptic disorders.